Thoughts on the standardization evolution of 5G NTN network architecture - Jiancheng SUN; Jiaying SUN; Deshan MIAO; Chunlin LI (Dianxin kexue)
In recent years, 5G has been commercialized around the world in a large scale.However, considering the cost and geographical restrictions, traditional 5G networks still have trouble in providing seamless global communication.To reach the global area coverage, satellite and 5G technology integration has become a new hot topic in the communication industry.In 3GPP, the first release of 5G NTN technical specifications based on transparent payload architecture has been completed.Firstly, the standardization status of 5G NTN network architecture was introduced.Secondly, the shortcomings or issues existing in the current network architecture of 5G NTN were analyzed.Finally, three 5G NTN network architecture enhancement and optimization schemes were proposed, which including IAB-based network architecture, NTN adaptive network architecture and NTN multi-connection network architecture for intersatellite link construction and data shunt.The proposed architectures aim to providing valuable suggestions and references for the subsequent research, standardization and network deployment of 5G NTN.